Squalenoylated Nanoparticle Pro-Drugs of Adjuvant Antitumor 11α-Hydroxyecdysteroid 2,3-Acetonides Act as Cytoprotective Agents Against Doxorubicin and Paclitaxel - Vágvölgyi, Máté; Bélteky, Péter; Bogdán, Dóra; Nové, Márta; Spengler, Gabriella; Latif, Ahmed D.; Zupkó, István; Gáti, Tamás; Tóth, Gábor; Kónya, Zoltán; Hunyadi, Attila (Frontiers in Pharmacology, 2020)
Several ecdysteroid acetonides act as adjuvant chemo-sensitizing agents against various cancer cell lines, and they can be formulated to self-assembling nanoparticle (NP) pro-drugs through a hydrolysable conjugation with squalene. In the bloodstream such squalenoylated nanoparticles dissolve into low-density lipoprotein (LDL) that allows targeting tissues containing high levels of LDL-receptors. In this work, ajugasterone C 2,3;20,22-diacetonide (3) and 11α-hydroxypoststerone 2,3-acetonide (4) were squalenoylated to obtain two new ecdysteroid pro-drugs (6 and 7) and their nano-assemblies (6NP and 7NP). A complete NMR signal assignment of 6 and 7 was achieved. Interaction of compounds 3 and 4 with chemotherapeutics was studied by the Chou-Talalay method. Compound 3 showed strong synergism with doxorubicin on a multi-drug resistant lymphoma cell line. In contrast, its nanoassembly 6NP significantly decreased the cytotoxicity of doxorubicin on these MDR cells, strongly suggesting that at least the 2,3-acetonide group was cleaved by the acidic pH of lysosomes after endocytosis of the prodrug. Further, compound 4 acted in strong antagonism with paclitaxel on MCF-7 cells and its nanoassemby 7NP also protected MCF-7 cells from the effect of paclitaxel. Our results suggest that acid-resistant A-ring substitution would be crucial to design adjuvant antitumor squalenoilated ecdysteroid prodrugs. Additionally, our results may be considered as a serendipitous discovery of a novel way to deliver cytoprotective, adaptogen ecdysteroids to healthy tissues with upregulated LDL-R.